A challenging pacemaker implantation in the presence of a giant right coronary aneurysm compressing the right atrium - Stefano Maffè (PAGEPress Publications, 2021)
Giant coronary artery aneurysm is an uncommon disease, treated with surgical intervention or percutaneous coil embolization. A thrombosed aneurysm can cause extrinsic compression on the cardiac chambers, with potential hemodynamic effects and may cause problems when we need to implant a cardiac device. We present a case of difficult pacemaker implantation in a patient with 3 syncopes, first-degree AV block and complete left bundle branch block on electrocardiogram. The patient presented a giant aneurysm of the right coronary artery (85 x 90 mm), thrombosed, with right atrial compression. The pacemaker implantation was hampered by the difficulty of passing the lead through the compressed right atrium; indeed, only with   simultaneous echocardiographic and fluoroscopic guidance, was it possible to complete the procedure. This case demonstrates the utility of echocardiogram, in particular settings, in cardiac stimulation procedures.